2020
DOI: 10.1130/ges02173.1
|View full text |Cite
|
Sign up to set email alerts
|

The Chief Joseph dike swarm of the Columbia River flood basalts, and the legacy data set of William H. Taubeneck

Abstract: The Miocene Columbia River Basalt Group (CRBG) is the youngest and best studied continental flood basalt province on Earth. The 210,000 km3 of basaltic lava flows in this province were fed by a series of dike swarms, the largest of which is the Chief Joseph dike swarm (CJDS) exposed in northeastern Oregon and southwestern Washington. We present and augment an extensive data set of field observations, collected by Dr. William H. Taubeneck (1923–2016; Oregon State University, 1955–1983); this data set elucidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 125 publications
(183 reference statements)
1
43
0
Order By: Relevance
“…We speculate that CRFB magmatism transiently increased the regional geothermal gradient (e.g., Murray et al, 2018), sufficiently raising the background temperatures to produce the observed apatite He age pattern next to the Maxwell Lake dike without resetting apatite He ages across the Wallowa Mountains region (Crowley and Reiners, 2001). Maxwell Lake lies within a region containing a large spatial density of CRFB dike segments exposed at the surface, with ∼ 5 segments per km 2 (Morriss and Karlstrom, 2018). If most segments are Grande Ronde age, recent dating (Kasbohm and Schoene, 2018) implies an eruptive flux of ∼ 1 km 3 /yr.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We speculate that CRFB magmatism transiently increased the regional geothermal gradient (e.g., Murray et al, 2018), sufficiently raising the background temperatures to produce the observed apatite He age pattern next to the Maxwell Lake dike without resetting apatite He ages across the Wallowa Mountains region (Crowley and Reiners, 2001). Maxwell Lake lies within a region containing a large spatial density of CRFB dike segments exposed at the surface, with ∼ 5 segments per km 2 (Morriss and Karlstrom, 2018). If most segments are Grande Ronde age, recent dating (Kasbohm and Schoene, 2018) implies an eruptive flux of ∼ 1 km 3 /yr.…”
Section: Discussionmentioning
confidence: 92%
“…The Maxwell Lake dike has been geochemically linked to the Wapshilla Ridge member of the Grande Ronde formation (Petcovic and Dufek, 2005), the single most voluminous eruptive unit preserved in the CRFB (5−10×10 3 km 3 erupted in multiple events contained within Wapshilla Ridge). However, macroscale structural characteristics of the Maxwell Lake dike are similar to thousands of other Chief Joseph Dike Swarm segments in the region as illustrated in Figure 1 (Taubeneck, 1970;Morriss and Karlstrom, 2018). Without petrographic and textural indicators of partial melt in the granitic host rocks that indicate prolonged magma flow and careful geochemical fingerprinting, it would be challenging to identify this segment as a prominant feeder of CRFB flows.…”
Section: Discussionmentioning
confidence: 95%
“…2); and (2) early crustal extension in the northern and central Basin-and-Range generated structural elements with NNE trends, but coeval magmatic intrusion along the Nevada-Columbia Basin Magmatic Belt generated dikes with NNW trends, a 45° difference (e.g., Colgan, 2013). Camp et al (2015) and Morriss et al (2020) attributed the source of these magmatic trends instead to a bottom-up process of forceful dike injection due to high magma overpressure unrelated to regional stress.…”
Section: Plume Relationship To Regional Tectonics (17-15 Ma)mentioning
confidence: 99%
“…1), which may have played a role in the small climatic impact of the CRB through heating and contact metamorphism of the crust 4,5,8 . While many of the dikes are buried under the thick CRB lavas, recent uplift of the province in the east has exposed inner workings of the crustal dike system (down to ~2 km depth [15][16][17], allowing an insight into dike-crust interactions [18][19][20] . This unique setting shows that dikes intruded into a variety of rock types including earlier erupted CRB lavas, granitic batholiths, and Paleozoic metasedimentary rocks that often contain organic-rich shale and carbonates.…”
Section: Geologic Backgroundmentioning
confidence: 99%
“…This unique setting shows that dikes intruded into a variety of rock types including earlier erupted CRB lavas, granitic batholiths, and Paleozoic metasedimentary rocks that often contain organic-rich shale and carbonates. Dikes range in thickness from 1 to >100 m, although the distribution strongly peaks at ~8 m, and larger structures likely record multiple reoccupations 15,16 . Based on the number of segments exhibiting partial melt in host rocks 16 , an estimated 3% of all known dikes served as feeders for lava flows and long-lived transport was probably highly localized along strike 19 .…”
Section: Geologic Backgroundmentioning
confidence: 99%